AXIS – a data exchange architecture among heterogeneous data sources using XML documents - Sardi Mergen, Sérgio Luis (2002)
XML is quickly becoming the industry standard data exchange format for business applications. Since most of the data is stored in relational tables, there must be a way to transform relational data into XML. A problem that arises is the heterogeneity of the business partner’s databases that are involved in the process. For a XML document to be readable for every business associate relational database, a mapping must be provided to specify how a XML document fits a specific database model. This paper proposes an architecture (AXIS – Automatic XML Interchange System) that allows the creation of such mapping and, afterwards, the conversion of relational data to XML and back to relational data.